3D structured materials and devices for artificial photosynthesis. (27th April 2020) - Zhou, Han; Xiao, Chengyu; Yang, Zhiwei; Du, Yijia
Abstract: Artificial photosynthesis is an effective way to convert solar energy into fuels, which is of great significance to energy production and reduction of atmospheric CO2 content. In recent years, 3D structured artificial photosynthetic system has made great progress as an effective design strategy. This review first highlights several typical mechanisms for improved artificial photosynthesis with 3D structures: improved light harvesting, mass transfer and charge separation. Then, we summarize typical examples of 3D structured artificial photosynthetic systems, including bioinspired structures, photonic crystals (PC), designed photonic structures (PC coupling structure, plasmon resonance structure, optical resonance structure, metamaterials), 3D-printed systems, nanowire integrated systems and hierarchical 3D structures. Finally, we discuss the problems and challenges to the application and development of 3D artificial photosynthetic system and the possible trends of future development. We hope this review can inspire more progress in the field of artificial photosynthesis.